2017
DOI: 10.3389/fpsyg.2017.01202
|View full text |Cite
|
Sign up to set email alerts
|

Does Promotion Orientation Help Explain Why Future-Orientated People Exercise and Eat Healthy?

Abstract: A study with United States undergraduate students showed individuals high in concern with future consequences engage in exercise and healthy eating because they adopt a promotion orientation, which represents the extent to which individuals are inclined to pursue positive gains. The present article reports a cross-cultural replication of the mediation findings with undergraduate samples from Brazil and New Zealand. Promotion orientation mediated the association between concern with future consequences and exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…Regular smokers are more likely to have low oxygen levels in their organs [71][72][73], making them prone to exhaustion and discouraging them from exercise. Lastly, our finding on the myopic view of the future is consistent with Adam and Nettle [74] and Milfont et al [75], who find that forward-thinking people are more likely to exercise. Intrinsically, such people are more likely to be concerned about future consequences.…”
Section: Discussionsupporting
confidence: 91%
“…Regular smokers are more likely to have low oxygen levels in their organs [71][72][73], making them prone to exhaustion and discouraging them from exercise. Lastly, our finding on the myopic view of the future is consistent with Adam and Nettle [74] and Milfont et al [75], who find that forward-thinking people are more likely to exercise. Intrinsically, such people are more likely to be concerned about future consequences.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are inconsistent with other studies. For the myopic view of future variable, Adams and Nettle [91] and Milfont et al [92] found a positive relationship between forwardthinking and physical activity. Meanwhile, Hunter et al [93] found a specific relationship between risk preference and physical activity.…”
Section: Discussionmentioning
confidence: 96%
“…Many cross-cultural replications have been published in this journal (e.g., Gabriel et al, 2001; Irwin, Engle, Klein, & Yarbrough, 1976; Milfont, Sibley, & Duckitt, 2010; Vauclair, Hanke, Fischer, & Fontaine, 2011) and elsewhere (e.g., Ekman & Heider, 1988; Milfont, Vilar, Araujo, & Stanley, 2017; Sidanius, Levin, Liu, & Pratto, 2000). However, there has been an increased focus on replication in recent years, and several large projects have started to investigate the reproducibility of psychological findings.…”
Section: Replication In Psychologymentioning
confidence: 99%